Gender systems in the Putin autocracy - Wood, Elizabeth A. (Frontiers in Sociology, 2024)
Over the last 23 years Russian President Vladimir Putin's autocracy has revealed a set of interlocking gender systems that have come to the fore particularly vividly since the fullscale invasion of Ukraine on February 24, 2022. How, this article asks, have the masculinist cultural and political practices of the Putin regime undermined democratic practices and engagement broadly speaking? How have they organized Russian state and society in ways that have led to today's war in Ukraine with its massive destruction, violence, and brutality? And have there been earlier signals that should have warned observers that this regime might undertake such a war of aggression? Drawing on public, mass media data, this article analyzes the gendered structures of power in Russia that have contributed to the degeneration of democracy in three main areas: 1) maleon-male domination in discourse and practice that supports Putin's personal rule and emasculates his enemies; 2) the elevation of male power clans, including the President's personal praetorian guard and the Russian private military companies; and 3) the overall taming and emasculation of the Russian Parliament combined with the elevation of tough women deputies, whom I call the Baba Commissars. These female MPs support the President's domination by creating an appearance of a threatening outside world that needs to be kept at bay. At the same time, they support a neo-gender order with women managing the house under the direction of the patriarchal male leader.